1996
DOI: 10.3382/ps.0751092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-Carotene, Canthaxanthin, Lutein, and Vitamin E on Neonatal Immunity of Chicks When Supplemented in the Broiler Breeder Diets

Abstract: The study was designed to assess neonatal immunity of chicks hatched from breeders fed diets supplemented with beta-carotene, canthaxanthin, lutein, or vitamin E. Broiler breeder birds were fed experimental diets consisting of control, 0.04% beta-carotene, 0.04% canthaxanthin, 0.04% lutein, 0.03% alpha-tocopherol acetate, or 0.04% beta-carotene plus 0.03% alpha-tocopherol acetate. Three weeks after initiation of experimental feeding, birds were vaccinated against Newcastle disease virus. Chicks hatched from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 19 publications
(25 reference statements)
4
81
0
Order By: Relevance
“…Accordingly, female American kestrels with better pre-laying body condition lay larger eggs and that egg size correlates positively with clutch size (Wiebe & Bortolotti 1995). In other bird species, physiologically active compounds derived from maternal diets are known to be incorporated into their eggs and subsequently enhance the immunocompetence of neonates (Haq et al 1996;Pastoret et al 1998;Surai et al 1998;Royle et al 1999). In addition, as both clutch size (Stearns 1992) and immunocompetence (Pastoret et al 1998) have a genetic basis, these traits could covary through selection for good genes.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, female American kestrels with better pre-laying body condition lay larger eggs and that egg size correlates positively with clutch size (Wiebe & Bortolotti 1995). In other bird species, physiologically active compounds derived from maternal diets are known to be incorporated into their eggs and subsequently enhance the immunocompetence of neonates (Haq et al 1996;Pastoret et al 1998;Surai et al 1998;Royle et al 1999). In addition, as both clutch size (Stearns 1992) and immunocompetence (Pastoret et al 1998) have a genetic basis, these traits could covary through selection for good genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was considerable variation among sites in the range of antioxidant concentrations recorded (figure 2), and some of this variation may be accounted for by the patchy distribution of high levels of radiation in the Chernobyl region, even on a micro-geographical scale (Shestopalov 1996). Such depression of dietary carotenoids deposited into yolk can increase the susceptibility of embryonic tissues to free-radical attack (Surai & Speake 1998), and reduce hatchling immune function (McWhinney et al 1989;Haq et al 1996). Avian embryos and hatchlings are particularly in need of antioxidants because their rapid metabolism incurs high rates of free-radical production, and their tissues are rich in unsaturated lipids that are particularly susceptible to free-radical attack (Surai et al 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, our findings diverge from those of mammal studies (Jyonouchi et al, 1994;Kim et al, 2000a;Kim et al, 2000b), where lutein supplementation has been shown to enhance immunoglobulin (IgG) production and/or T-cell proliferation. In chickens, lutein supplementation affected PHA-stimulated lymphocyte proliferation (Selvaraj et al, 2006), whereas no effect of antibody production against KLH (Selvaraj et al, 2006) or Newcastle disease virus (Haq et al, 1996) was detected. In moorhen (Gallinula chloropus) chicks, canthaxanthin supplementation enhanced PHA-response (Fenoglio et al, 2002).…”
Section: Effects Of Carotenoid Supplementationmentioning
confidence: 99%